Moldova : Accounting and Auditing - World Bank (Washington, DC, 2013)
Financial reporting and auditing practices in Moldova's corporate sector are currently in a period of transition from providing for tax calculation and statistical needs to convergence with International Financial Reporting Standards (IFRS) and International Standards on Auditing (ISA). This report draws upon recent international experience in developed economies and EU accession countries as well as expected amendments to EU Directives. The review found that, except in the banking sector, the current level of compliance with financial reporting obligations is inadequate, and that the quality of the financial reporting is low. In that context, the report recommends the following actions: (i) the capacity of regulatory agencies for enforcing accounting standards and financial reporting requirements to all entities of public interest - including large state-owned enterprises - should be increased; (ii) a public registry should be set-up for all public-interest companies to file their financial statements; and (iii) an independent oversight board of auditors should be established under the soon-to-be-issued new Audit Law, with the function to qualify statutory auditors, adopt auditing standards and develop guidelines, and monitor auditors compliance with NSA and independence requirements.